2005
DOI: 10.1021/es051114j
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Landfill Gas Quality as a Result of Controlled Air Injection

Abstract: Air addition has been proposed as a technique for rapid stabilization of municipal solid waste (MSW) in landfills. The objective of this study was to observe the change in concentration of trace constituents of landfill gas in response to air addition. Air injection tests were conducted at a MSW landfill in Florida, and the concentrations of several gaseous constituents at adjacent wells within the waste were measured. The concentrations of methane, carbon dioxide, and oxygen, as well as several trace constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Berge et al (2006) confirmed that ammonia was greatly reduced when recycled leachate passed through landfilled compost layers with continuous ventilation, with nitrate quantity in the effluent obviously less than the corresponding reduced ammonia, suggesting there were nitrification and denitrification simultaneously in the ventilated layers. Powell et al (2006) also observed the in situ nitrification and denitrification in an aerobic bioreactor landfill, with N 2 O kept low as in an anaerobic landfill.…”
Section: Introductionmentioning
confidence: 68%
“…Berge et al (2006) confirmed that ammonia was greatly reduced when recycled leachate passed through landfilled compost layers with continuous ventilation, with nitrate quantity in the effluent obviously less than the corresponding reduced ammonia, suggesting there were nitrification and denitrification simultaneously in the ventilated layers. Powell et al (2006) also observed the in situ nitrification and denitrification in an aerobic bioreactor landfill, with N 2 O kept low as in an anaerobic landfill.…”
Section: Introductionmentioning
confidence: 68%
“…The increase in CO was dramatic, raising concerns over the occurrence of incomplete combustion in the waste. There was no evidence of any change of N 2 O and VOCs concentrations [115].…”
Section: Quality Of Lfgmentioning
confidence: 83%
“…In the previous research conducted by Staley et al (2006); Komilis et al (2004), toluene, ethylbenzene, and xylene were also detected during FW anaerobic or aerobic decomposition. However, these aromatic pollutants were usually considered to be directly volatilized from waste mass (Powell et al, 2005), and the higher the fat content present, the more aromatics will be released (Heikes et al, 1995). Hence, for this FWTP, it is difficult to deduce which factor, between stripping and decomposition from lipid and lignin, mainly affects aromatic hydrocarbons emission.…”
Section: Voc Profilesmentioning
confidence: 99%